Mapping Gender Differences in Cardiovascular Disease and Diabetes Care - Bird, Chloe E. (RAND Corporation, 2014)
The care women receive for cardiovascular disease (CVD) and diabetes—and their health outcomes—continue to lag behind those of men, even for routine care. Awareness of and action to address gender gaps in women’s CVD care are limited, in part, because quality of care is not routinely measured and reported by gender. This pilot project describes and maps gender differences in CVD and diabetes care using data from a large health plan.